Tibetan e-grade present stems - Hill, Nathan (Research Institute for Languages and Cultures of Asia and Africa, Tokyo University of Foreign Stud, 2026)
Tibetan verbs with the root vowel -a- exhibit several ablaut patterns in their stem variations. Traditionally, these stem alternations are seen as recent developments, not valuable for reconstructing the Trans-Himalayan verbal system (Coblin 1976). Some verbs retain -a- in the present (e.g., √cag break’, pres. ḫchag), others have -e- (e.g., √bya do’, pres.byed), and some -o- (e.g., √sad kill’, pres. gsod). The traditional analysis attributes present -e- to a suffix -d (*byad > byed) and present -o- to a prefix g- (*gsad > gsod). I previously rejected this explanation for presents in -o- (Hill 2019b); here I address those in -e.
Old Tibetan Studies in Honor of Tsuguhito Takeuchi and Helga Uebach: Proceedings of the panel Old Tibetan Studies VII, Prague 2022
PUBLISHED
Tokyo